Pengujian Konsorsium Mikroba dalam Upaya Menekan Intensitas Penyakit Hawar Daun (Botrytis squamosa Walker.) pada Tanaman Bawang Merah (Allium ascalonicum L.) - LILIS IRMAWATIE; IDA ADVIANY; DICK DICK MAULANA; WILDA AULA LAILA ZAKIYYA KHAIRI (Fakultas Pertanian Universitas Udayana, 2023)
Microbial Consortium Testing to Reduce the Intensity of Leaf Blight (Botrytis squamosa Walker.) on Shallots (Allium ascalonicum L.). Shallots (Allium ascalonicum L.) are a popular horticultural crop that has been grown for centuries. One of the diseases that target the leaves of the shallot plant is Botrytis squamosa Walker. A microbial community is being used to reduce the severity of the fungus Botrytis squamosa Walker's disease. The goal of this study was to see how the microbial consortium affected the severity of leaf blight on shallot plants. The shallot cultivar Batu Ijo was employed in this investigation. This study was carried out at Margaasih Village, Cicalengka District, Bandung Regency, from March to June 2022. The Randomized Block Design (RBD) approach was employed in this investigation, which included 5 treatments and 5 replications. Microbiological consortium package A, microbial consortium package B, microbial consortium package C, microbial consortium package D, and controls were utilized in the treatments. This observation yielded parameters such as attack intensity, plant height, number of tubers, and tuber weight. The results demonstrated that the package B microbial consortium, which included the microorganisms Trichoderma sp. and Gliocladium sp. could suppress the severity of leaf blight (Botrytis squamosa Walker.)